The history of cocaine in medicine and its importance to the discovery of the different forms of anaesthesia - Grzybowski, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The first description of the use of cocaine by humans can be found in the memoirs of the Florentine traveller Amerigo Vespucci (1451-1512). For the next 300 years mostly the advantages of cocaine use, also as a medication, were emphasized. In 1860 Albert Niemann (1834-1861) isolated an active ingredient of coca leaves, which he named cocaine. After his death, his work was carried on by his disciple Wilhelm Lossen (1838-1906), who finally, in 1865, determined its proper chemical formula. Although the first observations concerning the effect of cocaine on mucous membranes were made by Niemann and Lossen, the first experimental studies involving the application of cocaine to animals were performed by the Peruvian surgeon Moréno y Maïz. In 1880 Basil von Anrep (1852-1925) published the results of his studies concerning the application of cocaine to humans. In the conclusion of his work he recommended cocaine as a surgical anaesthesia. But it was finally Carl Koller (1857-1944) who, in 1884, empirically demonstrated the benefits of cocaine use in medicine, most of all in ophthalmology. Subsequently, within a couple of months, the medical world learnt about and got interested in the use of cocaine for local anaesthesia. William Stewart Halsted (1852-1922) and his collaborator Richard John Hall (1856–1897) began their own research on cocaine injections. Eventually they developed the nerve and regional blocking techniques. Nowadays, due to the potential harmful effects of cocaine and the risk of addiction, the indications for the use of cocaine as an anaesthetic are strictly limited.